Spiritual Resilience: Navigating College Stress with Religious Support - Magen Branham; Elizabeth Valenti (Journal of Scholarly Engagement)
This study examines the relationship between religious support and stress in college students, focusing on the challenges of the college transition period. The research explores the potential role of religious support in mitigating stress, building on previous findings linking religiosity to coping skills and well-being. Incorporating a convenience sample (N=188) of college students from a private Christian University who identified as religious, the study employed a bivariate Pearson r correlation to examine the relationship between religious support and stress. Results revealed a negative relationship between the variable and highlighted the significance of religious support in alleviating stress during the critical college transition phase. The findings contribute to understanding the potential benefits of incorporating religious and spiritual factors in stress-reduction interventions for college students, emphasizing the importance of addressing stress for overall well-being and academic success.